The problem of credit in research evaluation – the case of Economics - Crespo, N.; Simões, N. (Annals of Library and Information Studies, 2021)
The measurement of scientific performance is usually done giving the full credit of each paper to all its authors. Aiming to analyze the impact of the number of authors on the performance, we propose an adjustment to the h-index that is flexible enough to allow the consideration of distinct co-authorship weighting schemes. We then evaluate the publication performance of the members of the departments of economics of the top 10 world universities. Our results show that the number of authors per paper is rapidly increasing and that this dimension measurably affects the final ranking of authors even in a subject area where the average number of authors is lower than in physical and life sciences.